2015
DOI: 10.1152/ajprenal.00512.2014
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin pretreatment of human adipose tissue-derived mesenchymal stromal cells enhances their prosurvival and protective effects on human kidney cells

Abstract: Zhao J, Young YK, Fradette J, Eliopoulos N. Melatonin pretreatment of human adipose tissue-derived mesenchymal stromal cells enhances their prosurvival and protective effects on human kidney cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…After 4 hr of treatment, we found that 100 and 1000 μ m melatonin treatment conferred significant protective effect against HG/HF‐induced damage ( P < 0.05, compared with the HG/HF+SIR group). Based on the experimental data and the previous literature , the dose of 100 μ m was used in this experiment. We evaluated melatonin's protective effect on SIR‐treated cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
“…After 4 hr of treatment, we found that 100 and 1000 μ m melatonin treatment conferred significant protective effect against HG/HF‐induced damage ( P < 0.05, compared with the HG/HF+SIR group). Based on the experimental data and the previous literature , the dose of 100 μ m was used in this experiment. We evaluated melatonin's protective effect on SIR‐treated cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The therapeutic mechanism of mesenchymal stem cells against AKI comprises both differentiation-dependent mechanism and differentiation-independent mechanism 42 43 44 . However, which of these two mechanisms is more significant for the therapeutic action of UC-MSCs against AKI remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a number of studies using rat models showed that melatonin could not only provide protection against acute kidney injury and partially reverse it [314], but also exert its protective effects on chronic kidney disease by scavenging free radicals [315], attenuating the chronic inflammation and limiting apoptosis [316]. Furthermore, an in vitro study found that melatonin pretreatment (100 μM) of human adipose tissue-derived mesenchymal stromal cells could improve their renoprotective and prosurvival effects on human kidney cells [317]. Moreover, it was found that the melatonin levels during pregnancy and labor were elevated and significantly higher than those after birth [318], and studies on pregnant rats indicated that melatonin interacted with other hormones and played a role as a triggering labor contributor [319].…”
Section: Bioactivities Of Melatoninmentioning
confidence: 99%